FORMATION OF CONSUMER ATTITUDE THROUGH CAUSED RELATED MARKETING ACTIVITY IN HEDONIC AND LOW INVOLVEMENT PRODUCT - Singgih Santoso (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2013)
Marketing activity that involving social organization, called cause related marketing (CRM), it popularly applied on so many product and service marketing activity. Using signal theory, this research empirically test consumer’s attitude establishment in two different brands that alliance to each other, also the impact to consumer’s purchase intentions. Research design was experimental research with 2 x 2 factorial designs. Experimental activity involved two different kinds of brand which were including to experience product, hedonic product, and low involvement, which are Cofeemix instant coffee and Van Houten chocolate bar, with two different social organizations, Greenpeace and WALHI. Research finding showed that the activity of CRM effectively influence on consumers' purchasing intentions for those brands; even though the variable of consumer’s attitudeAktivitas pemasaran yang melibatkan organisasi social disebut cause related marketing (CRM). Penelitian ini menggunakan teori sinyal dan menguji secara empiris sikap konsumen terhadap dua merek, yaitu produk hedonic dan prduk low involvement. Organisasi social yang digunakan ada dua yaitu Greenpeace dan WALHI. Penelitian dilakukan dengan metode eksperimen 2 x 2 desain factorial dengan menggunakan dua merek yaitu Coffeemix instant dan coklat Van Houten dalam setting dua perusahaan yang berbeda. Hasil penelitian menunjukkan bahwa CRM secara efektif mempengaruhi niat membeli konsumen untuk kedua merek tersebut.